N-(4-chloro-2-nitrophenyl)-N-methyl-N′-(quinolin-4-ylmethylene) hydrazine - Karadayi, N; Aydemir, E; Kazak, C; Kirpi, E; Tugcu, FT; Gümüs, MK; Kaban, S (INT UNION CRYSTALLOGRAPHY, 2005)
In the title compound, C17H13ClN4O2, the dihedral angle between the benzene and quinoline ring systems is 20.95 ( 4)degrees. C-(HO)-O-... and C-(HN)-N-... hydrogen bonds, as well as pi-pi stacking interactions, are observed in the crystal structure.
Keywords: Crystallography